Endotension-related aortic sac rupture treated by endograft relining. (April 2013) - Filippi, F; Tirotti, C; Stella, N; Rizzo, L; Taurino, M
Endovascular aortic aneurysm repair is an effective alternative to open surgical repair in high risk patient. Endotension is an unpredictable late and rare complication of EVAR. Clinical significance and choice of technique for treatment are controversial. At present, there are no cases of endotension-related aneurysmal sac rupture reported in literature, altough it is frequently associated with late surgical conversion. In this case report is described a case of a patient treated with a first generation Gore Excluder™ endograft for abdominal aortic aneurysm, with late aneurysmal sac enlargement without evidence of endoleak and subsequent contained rupture without anemia and shock. We have successfully treated the patient by endovascular procedure, through bilateral percutaneous femoral approach, with relining technique. Three years CT scan follow-up showed the endograft patency and size sac reduction.